EDUCAÇÃO BILÍNGÜE: A ESCUTA DA VOZ DA COMUNIDADE - Mota, Kátia Maria Santos (Intercâmbio, 2010)
The questions of identity and social inclusion are the center of the current educational debate on worldwide immigrant children. With focus on Brazilian second generation of immigrants in the United States, this text describes the experiences of two communities in Massachusetts concerning Bilingual Education programs.